EFFECT OF REPLACEMENT NITRITE BY BEET ROOT AND SILYBUM MARIANUM POWDER IN PHYSICAL CHARACTERISTICS AND LIPID OXIDATION FOR PASTERMA - Zaid I.H Zainy,; A. M. Alrubeii, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This study was aimed to decreasing the use of nitrite in Pasterma (sausage in Iraq) in traditional condition, beetroot and milk thistle was used with (75% veal meat and 25% pelvic and kidney fat),the treatment were divide (T1): (0.075 ppm milk thistle with 0.075 ppm beetroot), (T2): (0.075 ppm nitrite with 0.075 ppm milk thistle powder),(T3): (0.075 ppm nitrite with 0.075ppm beetroot powder), (T4):Addition of the synthetic antioxidant Betalyted Hydroxy Anisole (0.01%) BHA. The physical properties resulted in cooking loos, WHC, T3the treatment excelled (8.17)%and 39.12% respectively, Fat oxidation measurements (TBA 3.02 Malone Didehyde/kg, and peroxide value 0.56 mEq/kg fat) inT3 sample show significant differences the best value ,the result are consistent with the measurements reducing power assay and DPPH – assay it was better in T3.